Studi Kontribusi Workplace Spirituality terhadap Employee Well-Being pada Dosen Wanita - Amalia Nur'aini Widyasari; Ali Mubarak (Bandung Conference Series: Psychology Science, 2024)
Abstract. Workplace spirituality is the understanding of individuals as spiritual beings whose who need nurturing at work, with purpose and meaning in their work, and having a feeling of connection with others or the community at work (Ashmos & Duchon, 2000). Employee well-being is employee well-being related to employee feelings about satisfaction at work which can affect employee goals in showing the results achieved from their work (Page and Vella-Brodick, 2009). The purpose of the study was to examine how much workplace spirituality contributes to employee well-being in female lecturers at religious-based private universities in Bandung City. Using cross sectional study with multiple regression data analysis. The measuring instrument used is the Workplace Spirituality Scale by Ashmos & Duchon (2000) which has been adapted into the Indonesian version by Mubarak et al., (2022), while employee well-being uses the Employee Well-Being Scale (EWBS) measuring instrument developed by Zheng et al. (2015) which has been adapted into the Indonesian version by Rahmi et al., (2021). The results showed 96.3% of female lecturers had high workplace spirituality and 86.1% of female lecturers had high employee well-being. In this study, workplace spirituality contributed 53.1% to employee well-being. Abstrak. Workplace spirituality adalah Pemahaman individu sebagai makhluk spiritual yang jiwanya membutuhkan pemeliharaan di tempat kerja, dengan tujuan dan makna pada pekerjaannya, dan memiliki perasaan terhubung dengan orang lain atau komunitas di tempat kerja (Ashmos & Duchon, 2000). Employee well-being adalah Kesejahteraan karyawan terkait perasaan karyawan mengenai kepuasaan saat bekerja yang dapat mempengaruhi tujuan karyawan dalam menunjukan hasil yang diraih dari pekerjaannya (Page dan Vella-Brodick, 2009). Tujuan penelitian untuk menguji seberapa besar kontribusi workplace spirituality terhadap employee well-being pada dosen wanita di perguruan tinggi swasta berbasis agama di Kota Bandung. Menggunakan metode kuantitatif kausalitas dengan analisis data regresi berganda. Alat ukur yang digunakan adalah Workplace Spirituality Scale oleh Ashmos & Duchon (2000) yang telah diadaptasi ke dalam versi Bahasa Indonesia oleh Mubarak et al., (2022), sedangkan employee well-being menggunakan alat ukur Employee Well-Being Scale (EWBS) yang dikembangkan oleh Zheng et al. (2015) yang telah diadaptasi ke dalam versi Bahasa Indonesia oleh Rahmi et al., (2021). Hasil penelitian menunjukkan 96.3% dosen wanita memiliki workplace spirituality yang tinggi dan 86.1% dosen wanita memiliki employee well-being yang tinggi. Dalam penelitian ini workplace spirituality memberikan kontribusi sebesar 53,1% terhadap employee well-being.